Innovation and education: Is there a "nerd effect"? - Stefan Goldbach (Technische Universität Darmstadt, Department of Law and Economics, 2012)
This paper investigates whether entrepreneurs with technical education are more innovative in high-tech industries than economists. The main contribution to the literature is in using the type of education as main explanatory variable for innovation. To analyze this question, the KfW/ZEW Start-Up Panel between 2005 and 2007 is used. Two independent OLS regressions are conducted for entrepreneurs with university degree and practical education. The results suggest that education matters for individuals with a university degree in high-tech industries but not for people with practical education. Having an economics degree is correlated with higher innovativeness. Therefore, for the underlying sample we do not find a nerd effect. The results depend on the underlying definition of innovation, as robustness checks show.
Keywords: A20; L26; O32; 330; entrepreneurship; innovation; education; Unternehmer; Innovation; Bildungsabschluss; Technische Berufe; Ökonomen; Unternehmensgründung; Schätzung; Deutschland